Features of the Canoeists’ Special Physical Fitness at the Distance of 1000 m - Pengcheng Guo; Ziyang Zhang; Zijian Huang; Xianglin Kong; Andrii Diachenko; Olga Rusanova; Andrey Rusanov (Physical Education Theory and Methodology, 2022)
The aim of the study. To better understanding of the indicators of functional support for special endurance and physiological demands in canoeists at a distance of 1000 m.